LEKSIKON PAKAIAN ADAT PENGANTIN MELAYU PONTIANAK:TINJAUAN EKOLINGUISTIK - Bella Afrila Luciani; Ahmad Rabi’ul Muzammil; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to classify any lexicon, describe the form of the lexicon, and produce a form of supplementary Indonesian language learning text based on the lexicon of Pontianak Malay traditional wedding dress. The theory used is ecolinguistic theory. The method used in this study is a descriptive method with a qualitative form. The source of data in this study is the Pontianak Malay community, whose address is in the city of Pontianak. Data collection techniques are interview techniques, notes, records and documentation. This study resulted in 18 lexicon of Pontianak Malay traditional wedding dress. There are 4 types of lexicon groups, namely 7 lexicon in the form of traditional bridal attire, 11 lexicon in the form of traditional bridal clothing accessories, 7 lexicon in the form of traditional bridal clothing materials and 18 lexicon in the form of bridal traditional clothing how to use it. The forms of the lexicon are categorized based on the type, namely traditional bridal clothing, the material of which has 7 lexicon and traditional bridal clothing, how to use it, which has 18 lexicon. Each lexicon group is divided into 2 levels, namely the noun level there are 10 lexicon and the verb level 18 lexicon. In describing the traditional dress lexicon of the Pontianak Malay bride, using ecolinguistic parameters and the three dimensions of social praxis. The form of Indonesian language learning text based on the lexicon of Pontianak Malay traditional wedding dress produces descriptive text.Keywords: Ecolingistics, Lexion, Traditional Bridal Clothin